Intestinal absorption and bioavailability of traditional Chinese medicines: a review of recent experimental progress and implication for quality control - Liu, Jing-Yi; Lee, Kai-Fai; Sze, Cho-Wing; Tong, Yao; Tang, Sydney Chi-Wai; Ng, Tzi-Bun; Zhang, Yan-Bo (Journal of pharmacy and pharmacology, 2013)
Experimental studies on the pharmacokinetics of traditional Chinese medicines (TCMs) have achieved great progress in recent years. This review aims to summarize the progress made on intestinal absorption and bioavailability of TCMs, and proposes the application of intestinal absorption assays as new tools for the quality and safety control of these medicines. Since only the absorbed constituents may produce possible therapeutic effect (except those that directly target the digestive tract), intestinal absorption is of utmost importance for the drug action of TCMs, which are usually taken orally. Meanwhile, complicated drug interactions may occur among the multiple ingredients in a herbal mixture. In this regard, the intestinal permeability assays not only provide useful pharmacokinetic data of TCMs, but have potential applications for quality and safety control. Moreover, knockout animals, 2/4/A1 in-vitro cell model and physiologically-based in-silico models based on the online TCM database can be quite useful for the prediction of absorption and bioavailability of TCMs. A variety of in-vivo, in-vitro, in-situ and in-silico models for predicting the intestinal absorption and bioavailability can be applied to study the herbal interactions and screen appropriate biomarkers for the quality and safety control of TCMs.